2006
DOI: 10.1037/1040-3590.18.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Development of a measure of drinking and driving expectancies for youth.

Abstract: The present study constructs and provides initial validation for a measure of positive expectancies for drinking and driving for use with adolescents and young adults (PEDD-Y). In Study 1, items were generated through open-ended responses from high school- and college-age youth. Data collected from a 2nd sample of college students (n = 404) identified a 29 item, 4 factor questionnaire. Two of the PEDD-Y factors (Convenience, Avoiding Consequences) explained additional variance in drinking and driving behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 46 publications
(60 reference statements)
6
26
0
Order By: Relevance
“…These variables should also be taken into consideration as a screening procedure when designing training programs for teen drivers, so that the program could be created according to the characteristics of each type of drivers, predicting which drivers are at risk of driving under the influence of alcohol and, so, to be able to intervene in advance. Moreover, as attitudes can change due to experience, prevention and intervention, they seem to be a good target and outcome measure for intervention programs (Jewell et al, 2008;McCarthy et al, 2006). Additionally, as personality predicts adherence to intervention programs, it should be taken into account in order to promote criminal deterrence (Harkness & Lilienfeld, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These variables should also be taken into consideration as a screening procedure when designing training programs for teen drivers, so that the program could be created according to the characteristics of each type of drivers, predicting which drivers are at risk of driving under the influence of alcohol and, so, to be able to intervene in advance. Moreover, as attitudes can change due to experience, prevention and intervention, they seem to be a good target and outcome measure for intervention programs (Jewell et al, 2008;McCarthy et al, 2006). Additionally, as personality predicts adherence to intervention programs, it should be taken into account in order to promote criminal deterrence (Harkness & Lilienfeld, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…They provide information about accessible and consequently relevant health cognitions. Such responses are useful for identifying personally relevant issues for qualitative analysis and have been used effectively in questionnaire development (Leigh & Stacy, 1993;Markland & Hardy, 1993;McCarthy, Pedersen, Thompsen, & Leuty, 2006). The present method provides a valid and efficient coding procedure that reduces ambiguity and solves a critical problem in sociates correlate with corresponding levels of alcohol and marijuana use in the population of college students.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results, as well as results from longitudinal studies of adult driving-under-theinfl uence offenders (Greenberg et al, 2005), may indicate that these perceptions are not important determinants of drinking-and-driving decisions over time. Recent studies have indicated that perceptions about potential consequences are not as infl uential as perceived benefi ts in determining laboratory risk decisions (Gardner and Steinberg, 2005), risky driving (McKenna and Horswill, 2006), and driving after drinking (McCarthy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%